ASSESSMENT OF TEACHING PROFICIENCY USING QUALIMETRIC TECHNOLOGY - Sergeeva, Marina; Grishina, Irina; Karavanova, Lyudmila; Belokon, Olga; Serova, Lyudmila (Revista Inclusiones, 2020)
The relevance of studying the basic psychological and pedagogical principles of the formation and improvement of teaching proficiency in the current context is due to the social and applied value of the continuing professional development of the teacher. It should be emphasized that the theory of education and teaching practice are not being transformed synchronously, which causes certain contradictions. Therefore objective monitoring of teaching proficiency is required. Nowadays, Russian education is in dire need of teachers who can improve the educational process, offer effective original methods and concepts, master teaching tools, and improve the quality of services provided. Only a teacher who continuously enhances teaching proficiency can meet the challenges of professional reality. The task of encouraging the teacher to improve professional skills seems to be difficult to achieve. The teaching proficiency assessment system, which is currently operating in secondary and higher education institutions, only allows determining the current level of professionalism, but is not able to show the dynamics of changes and determine existing prospects. In this aspect, the monitoring of teaching proficiency with the use of a complex quantitative technology based on the concept of latent variables is of particular importance. The teacher should meet the requirements of the time, demonstrate teaching proficiency and creativity, which are based on professionally important qualities and pedagogical culture. Any teacher should adhere to a humanistic philosophy, consider a person as the highest value and appreciate the uniqueness of each student’s personality, build relationships based on respect and mutual trust.